FORMATION MODEL OF THE STUDENTS INTERCULTURAL SKILLS ON THE BASIS OF THE COMMUNICATIVE ETHNOGRAPHIC APPROACH AT STUDING OF FOREIGN LANGUAGE - Vemian, V. (Problems of Engineer-Pedagogical Education, 2021)
The article gives the definition of the communicative-ethnographic approach which is aimed at the formation of foreign language communicative competence.The author explores available theoretical developments in the area of intercultural competence of the students in the conditions of immersion in the authentic and socio-cultural environment. However, it is necessary to state about existence of a number has not yet developed and insufficiently studied questions of this aspect. As a rule, some aspects of introducing intercultural competence into the educational process are examined from the technical, technological and didactic view. Special attention is given to the topics that are directly included in the educational process or supporting its tasks, whose effectiveness can be increased. In addition, the several ways to implement this approach are proposed based on the development of intercultural skills. On the one hand. It is determined the range of the students intercultural skills developed on the basis of a communicative-ethnographic approach; It is established the psychological and pedagogical conditions for the development of the students intercultural skills on the basis of the communicative-ethnographic approach. On the other hand, a model for the development of intercultural skills of students has been developed on the basis of a communicative- ethnographic approach; Communicative and ethnographic approach is one of the modern cultural approaches aimed at the formation of foreign language communicative competence and intercultural competence which are studied in terms of immersion in an authentic linguistic and socio-cultural environment. The author describes linguodidactic characteristics in the communicative-ethnographic approach. The methodology for the development of the students intercultural skills on the basis of the communicative-ethnographic approach is substantiated in order to determine the effectiveness of the methodology for the development of the students intercultural skills on the basis of the communicativeethnographic approach.